A Novel Single Domain Antibody Targeting FliC Flagellin of Salmonella enterica for Effective Inhibition of Host Cell Invasion - Huen, Jennifer; Yan, Zhun; Iwashkiw, Jeremy; Dubey, Shraddha; Gimenez, Maria C.; Ortiz, Maria E.; Patel, Saumil V.; Jones, Michael D.; Riazi, Ali; Terebiznik, Mauricio; Babaei, Saeid; Shahinas, Dea (Frontiers in Microbiology, 2019)
The enteric pathogen, Salmonella enterica is a major cause of human gastroenteritis globally and with increasing bacterial resistance to antibiotics, alternative solutions are urgently needed. Single domain antibodies (sdAbs), the smallest antibody fragments that retain antigen binding specificity and affinity, are derived from variable heavy-chain only fragments (VHH) of camelid heavy-chain-only immunoglobulins. SdAbs typically contain a single disulfide bond simplifying recombinant protein production in microbial systems. These factors make sdAbs ideally suited for the development of effective anti-bacterial therapeutics. To this end, we generated an anti-Salmonella VHH library from which we screened for high affinity sdAbs. We present a novel sdAb (Abi-Se07) that targets the Salmonella virulence factor, FliC, required for bacterial motility and invasion of host cells. We demonstrate that Abi-Se07 bound FliC with a KD of 16.2 ± 0.1 nM. In addition, Abi-Se07 exhibited cross-serovar binding to both whole cells of S. enterica serovar Typhimurium, Heidelberg, and Hadar. Abi-Se07 significantly inhibited bacterial motility and significantly reduced S. enterica colonization in a more native environment of chicken jejunum epithelium. Taken together, we have identified a novel anti-Salmonella sdAb and discuss future efforts toward therapeutic development.